Analisis Terhadap Program Bantuan Sosial, Jaminan Sosial Dan Subsidi Di Kabupaten Tabalong - Hastutiningsih, Ida; Abidin, Abidin; Husni, Muhammad; Norlailah, Norlailah; Titasari, Andini Putri (STAI AL FALAH Banjarbaru, 2022)
The problem of inaccuracies in target recipient data still occurs in many regions in Indonesia. This is often complained of by the community and is one of the causes of the ineffectiveness of social assistance, social security, and subsidies that have been provided in alleviating poverty. The purpose of writing this article is to analyze the number of poor people and their welfare status based on the October 2020 DTKS data, to map the types and numbers of recipients of social assistance and Social Security and Subsidies in Tabalong Regency, and to analyze the database used for targeting beneficiaries. social security and social security and subsidies in Tabalong Regency. The method used is descriptive exploratory with a qualitative approach through FGD, interviews, comparative studies, and secondary data collection and processing. From the results of the recapitulation and analysis of the data obtained, it is known that there are various social assistance, social security, and subsidies received by the community in Tabalong Regency but there are different databases in determining target recipients in each sector. In addition to differences in the database, another difference found was the difference in the criteria for beneficiaries. So, to improve poverty reduction programs in Tabalong Regency, it is necessary to coordinate and synchronize in determining the criteria for the poor and develop a